2022
DOI: 10.1021/acs.jpclett.2c02203
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Orientation of 4f Magnetic Moments by Classical Photoemission

Abstract: To use efficiently the magnetic functionalities emerging at the surfaces or interfaces of novel lanthanides-based materials, there is a need for complementary methods to probe the atomic-layer resolved magnetic properties. Here, we show that 4f photoelectron spectroscopy is highly sensitive to the collective orientation of 4f magnetic moments and, thus, a powerful tool for characterizing the related properties. To demonstrate this, we present the results of systematic study of a family of layered crystalline 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our previous results for the antiferromagnet TbRh 2 Si 2 have shown that the line shape of the 4f photoemission (PE) spectrum is highly sensitive to the orientation of the long-range-ordered 4f magnetic moments allowing us to estimate their direction. , For example, for the Tb- and Si-terminated surfaces of TbRh 2 Si 2 , it was shown how strongly the changes of the CEF at the surface lead to a reorientation of the magnetic moments of Tb from the out-of-plane direction in the bulk (and below the Si surface) to the in-plane orientation observed on the Tb surface. , Thus, it is reasonable to assume that if the magnetically ordered system reveals a temperature-dependent canting of the 4f moments, then the respective properties may presumably be derived from the evolution of the line shape of the 4f multiplet, in particular in the vicinity of critical temperatures. To investigate this point and to understand how efficiently we may detect and characterize the canting from 4f PE spectra, we consider here the two antiferromagnetic (AFM) materials HoRh 2 Si 2 ( T N Ho = 29 K) , and DyRh 2 Si 2 ( T N Dy = 55 K). ,, Our magnetic susceptibility measurements show that both compounds reveal a temperature-dependent canting of the 4f magnetic moments which sets in at T i Ho = 11.5 K and T i Dy = 12 K for HoRh 2 Si 2 and DyRh 2 Si 2 , respectively.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous results for the antiferromagnet TbRh 2 Si 2 have shown that the line shape of the 4f photoemission (PE) spectrum is highly sensitive to the orientation of the long-range-ordered 4f magnetic moments allowing us to estimate their direction. , For example, for the Tb- and Si-terminated surfaces of TbRh 2 Si 2 , it was shown how strongly the changes of the CEF at the surface lead to a reorientation of the magnetic moments of Tb from the out-of-plane direction in the bulk (and below the Si surface) to the in-plane orientation observed on the Tb surface. , Thus, it is reasonable to assume that if the magnetically ordered system reveals a temperature-dependent canting of the 4f moments, then the respective properties may presumably be derived from the evolution of the line shape of the 4f multiplet, in particular in the vicinity of critical temperatures. To investigate this point and to understand how efficiently we may detect and characterize the canting from 4f PE spectra, we consider here the two antiferromagnetic (AFM) materials HoRh 2 Si 2 ( T N Ho = 29 K) , and DyRh 2 Si 2 ( T N Dy = 55 K). ,, Our magnetic susceptibility measurements show that both compounds reveal a temperature-dependent canting of the 4f magnetic moments which sets in at T i Ho = 11.5 K and T i Dy = 12 K for HoRh 2 Si 2 and DyRh 2 Si 2 , respectively.…”
mentioning
confidence: 99%
“…As we begin to gradually approach its surface, it is obvious that the magnetic properties of the RE layers may deviate more and more from those in the bulk. These changes of the surface-related properties can be related to the breaking of translational symmetry, relaxation and reconstruction, appearance of electronic surface states and resonances as well as changes of the CEF near and at the surface. The mentioned surface-related properties mayand in some cases quite dramaticallyaffect the magnetic properties of individual RE layers linked with the orientation of 4f magnetic moments. Thus, there is apparent need for a precise characterization of the orientation of magnetic moments as well as their possible canting away from the crystallographic axes in certain atomic layers of materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation